Effect of Spraying Gibberellic acid (GA3) , urea and zinc on some production indicators of Orange trees c.v.Valencia - ديب, علي; صهيوني, فهد; ابودرعى , عامر (Latakia University Journal -Biological Sciences Series, 2022)
This study was carried out in setkhiris village belonging to the countryside of latakia governorate during (2019) within the citrus field containing (40) orange trees of Valencia (late orange) and 20 years old and grafted on Citrus aurantium root stock ,to study the impact of spraying Gibberellin which its concentration 30 ppm and Urea 1% and zinc sulfate 0,4 % regarding the growing properties on the Valencia orange tree .The experiment was designing to randomized complete block design ,the experiment comprised of 8 treatments repeated 5 times and distributed randomly . The results showed that the impact spraying with GA 3 ,Urea and zinc on the trees individually or together was positive to reduce the percentage of the cluster of the yields with the value of 29.16% and the rest of the yields with the value of 58.4 fruit/tree and it was positive and led to increase in production and improve the physical properties of fruits, where this transaction gave better average for the tree production with the value of 255 kg production dunem with the value of 6871 kg / dunem .